Effect of Pad Surface Micro-Texture on Removal Rate during Tungsten Chemical Mechanical Planarization. (1st January 2016) - Mu, Yan; Han, Rouchen; Sampurno, Yasa; Zhuang, Yun; Philipossian, Ara
Abstract : This study investigated the effect of two conditioner discs (i.e. "Disc A" and "Disc B") during tungsten chemical mechanical planarization. Results showed that while pad temperature and removal rate increased with polishing pressure and platen velocity on both discs, "Disc B" generated consistently lower removal rates and coefficients of friction than "Disc A". To fundamentally elucidate the cause(s) of such differences, pad surface contact area and topography were analyzed using laser confocal microscopy. The comparison of the pad surface micro-texture analysis on pad surfaces conditioned by both discs indicated that "Disc A" generated a surface having a smaller abruptness (λ) and more solid contact area which resulted in a higher removal rate. In contrast, "Disc B" generated many large near-contact areas as a result of fractured and collapsed pore walls.